Recuperação de potássio da rocha verdete via reação com ácido sulfúrico em condições hidrotermais - Schimicoscki, Raquel Stavale (2019)
This work presents a study on the dissolution kinetics of a Brazilian glauconitic siltstone, known as Verdete, in the presence of sulfuric acid and in hydrothermal conditions. The objective was to verify the efficiency of the hydrothermal methodology in breaking up the structures of muscovite, glauconite and K-feldspar at low liquid/solid ratio to recover potassium. The water-soluble and insoluble products were analysed by flame photometry, XRD and SEM-EDS. The reaction rate of K extraction showed to be high, and K recovery was directly proportional to the acid concentration. K release occurred due to rupture of micas, and the reaction mechanism occurred through replacement of interlayer K+ with H+, and a partially extraction of Al3+, Fe3+, Fe2+ and Mg2+ from the 2:1 layer. With the breakup of silicate structures, the remaining solid product was amorphous silica. K-feldspar began to be dismantled at higher temperatures (> 473 K).